Manufacturing SMEs doing it for themselves: developing, testing and piloting an online sustainability and eco-innovation toolkit for SMEs. Issue 3 (3rd May 2020) - Mitchell, Sinéad; O'Dowd, Paul; Dimache, Aurora
ABSTRACT: Public discourse frequently cites the damaging activities of large organisations on global environmental issues, but smaller organisations are rarely, if ever, featured. Small and Medium Enterprises (SMEs) make up 99% of all businesses in the EU, cumulatively causing more industrial pollution and producing more waste than larger businesses. However, large companies are more likely to address sustainability issues than smaller ones. SMEs need help to change. In a collaborative approach, an online sustainability framework was developed to overcome the barriers contributing to the slow uptake in environmental management in SMEs. The views of owner-managers were incorporated throughout the development process. Best practice environmental tools and training were identified, which were designed in an SME-friendly way and made available online. This paper describes the development of the pilot Sustainability and Eco-Innovation (SEco) toolkit, followed by an analysis of its use. This research finds that a self-led toolkit was not enough to nudge SMEs to address environmental issues, despite being approved by owner-managers at each step.